Impact of copper sulfate application at an urban Brazilian reservoir: A geostatistical and ecotoxicological approach - Leal, P. R.; Moschini-Carlos, V. [UNESP]; López-Doval, J. C.; Cintra, J. P.; Yamamoto, J. K.; Bitencourt, M. D.; Santos, R. F.; Abreu, G. C.; Pompêo, M. L.M. (Elsevier, 2018)
A landscape ecotoxicology approach was used to assess the spatial distribution of copper in the recent bottom sediment (surficial sediment) of a Brazilian subtropical reservoir (the Guarapiranga reservoir) and its potential ecotoxicological impacts on the reservoir ecosystem and the local society. We discuss the policies and procedures that have been employed for the management of this reservoir over the past four decades. Spatial heterogeneity in the reservoir was evaluated by means of sampling design and statistical analysis based on kriging spatial interpolation. The sediment copper concentrations have been converted into qualitative categories in order to interpret the reservoir quality and the impacts of management policies. This conversion followed the Canadian Water Framework Directive (WFD) ecotoxicological concentration levels approach, employing sediment quality guidelines (SQGs). The SQG values were applied as the copper concentration thresholds for quantitative-qualitative conversion of data for the surficial sediment of the Guarapiranga. The SQGs used were as follows: a) interim sediment quality guideline (ISQG), b) probable effect level (PEL), and c) regional reference value (RRV). The quantitative results showed that the spatial distribution of copper in the recent bottom sediment reflected the reservoir's management policy and the copper application protocol, and that the copper concentrations varied considerably, ranging from virtually-zero to in excess of 3 gcopper/kgds. The qualitative results demonstrated that the recent bottom sediment was predominantly in a bad or very bad condition, and could therefore have impacts on the local society and the ecosystem. It could be concluded that the management policy for this reservoir was mainly determined by the desire to minimize short-term costs, disregarding long-term socioeconomic and environmental consequences.
Keywords: Copper sulfate; Geostatistics; Landscape ecotoxicology; Reservoir management policy; Sediment